A LEGAL PROTECTION OF MUSIC ROYALTY ON OPEN CONTENT LICENSE THROUGH SOUNDCLOUD - Sartika Nanda Lestari; Arifin Pringgo Laksono (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Public ownership in digital world enable anyone to access and use the available content including SoundCloud. SoundCloud provides music sharing services under an open content license by providing a platform for the content availability. This paper tries to investigate the use of open content licenses on SoundCloud and explain the legal protection of music royalties on open content licenses through SoundCloud. Employing normative juridical research methods, this paper makes use of secondary data (literature study). The results of the research show that the open content license is a license form that refers to a civil agreement that provide copyright protection in the digital world and provides royalty protection by determining how a work will be disseminated whether for commercial or non-commercial purposes. Keywords: copyrights, music royalties, open content license